Electric pulse-induced resistive switching in ceramic YBa2 Cu3 O7 - δ / Au interfaces - Acha, Carlos Enrique (2009)
We show the existence of a reversible, complementary and polarity dependant electric pulse-induced resistance (EPIR) switching effects in Au / YBa2 Cu3 O7 - δ ceramic superconductor interfaces. Non-volatile high and low resistance states and transition regions between them are obtained as a function of the amplitude and polarity of the pulsing voltage. Relaxation processes of the resistivity after applying the pulses, not associated with heating effects, are also observed. We also report on the temperature sensitivity of these resistance hysteresis switching loops, where both the difference between high and low resistance states and the voltage needed to produce the switching decrease with increasing temperature. Our results are consistent with a mechanism for the EPIR effect based on oxygen electromigration. © 2009 Elsevier B.V. All rights reserved.